1956
DOI: 10.1002/jsfa.2740070109
|View full text |Cite
|
Sign up to set email alerts
|

The metabolizable energy of poultry feeding stuffs in relation to their chemical composition

Abstract: The metabolizable energy values of 17 samples of cereals, cereal by-products and mixed rations have been determined with laying hens. They ranged from 1300 to 3500 kg.-cal. per kg. and, where comparison with the findings of other workers has been possible, agreement has been generally satisfactory. The same samples were subjected to the standard methods of proximate analysis, and also analysed for their content of starch and reducing sugars using a specially modified anthrone method. Statistical analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
130
1
1

Year Published

1961
1961
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(133 citation statements)
references
References 7 publications
1
130
1
1
Order By: Relevance
“…Glycerol used in this experiment contained 15.90 MJ ME/kg. ME levels of glycerol were estimated using Carpenter and Clegg's (1956) equation: ME (kcal/kg) = 53 + 38 [(CP, %) + (2.25 × ether extract, %) + (1.1 × starch, %) + (sugar, %)]. The experimental diets were formulated to be isocaloric and isonitrogenous.…”
Section: Methodsmentioning
confidence: 99%
“…Glycerol used in this experiment contained 15.90 MJ ME/kg. ME levels of glycerol were estimated using Carpenter and Clegg's (1956) equation: ME (kcal/kg) = 53 + 38 [(CP, %) + (2.25 × ether extract, %) + (1.1 × starch, %) + (sugar, %)]. The experimental diets were formulated to be isocaloric and isonitrogenous.…”
Section: Methodsmentioning
confidence: 99%
“…Titus (1958) extended and refined the work of Fraps et al (1940) by deriving a series of 'percentage multipliers' which permit calculation of the AME values of individual f'eedingstuffs. Opstvedt (1973) (Opstvedt 1976 (Janssen and Terpstra 1972;Jannsen et al 1975Jannsen et al , 1976Janssen 1916Janssen , 1919 (Connor et al 1976) and oats (Davidson et al 1978 Carpenter and Clegg (1956), Bolton (1962b) and Sibbald et al (1963) whereas the equations ofTitus (1958) produced reasonably accurate data (Guirguis 1975 Coates et al 1911a). No equation was able to give satisfactory TME values for wheats but the TME values of oats (Sibbald and Prtce l9lla) and barley (Sibbald and Price 1916b) were well predicted by some equations.…”
Section: Control Of Feed Intakementioning
confidence: 98%
“…However, according to Erbersdobler and Riedel (1912) Work with mice has shown that intestinal microflora alter cell renewal rates in the ileum (Abrams et al 1963), duodenal crypts (Lesher et al 1964) and small intestine (Khoury et al 1969 Yoshida et al (1965), Yoshida and Morimoto (1966,1970) and Squibb (1971 (1961) found the AME values of oats to increase with bushel weight; this was confirmed by Sibbald and Slinger (1963a), Sibbald and Price (1976a) but not by Salo (1978) whose AME values were calculated from chemical composition. The TME values of oats were related to bulk density (Sibbald and Price 1977a) as were ADE values measured with mice (Christison and Bell 1975 (Hochstetler and Scott 1975 Carpenter and Clegg (1956), Bolton (1962b) and Sibbald et al. (1963).…”
Section: Control Of Feed Intakementioning
confidence: 98%
“…The samples were ashed in a muffle furnace prior to the analysis of calcium and total phosphorus [11,12] . Metabolizable energy levels of samples were estimated using the Carpenter and Clegg's equation [13] .…”
Section: Measurements Sample Collection and Laboratory Analysismentioning
confidence: 99%